Targeting Glycogen Synthase Kinase 3 Beta Regulates CD47 Expression After Myocardial Infarction in Rats via the NF-κB Signaling Pathway - Xu, Li-Na; Wang, Shu-Hui; Su, Xue-Ling; Komal, Sumra; Fan, Hong-Kun; Xia, Li; Zhang, Li-Rong; Han, Sheng-Na (Frontiers in Pharmacology, 2021)
The aim of this study was to investigate the effects of the GSK-3β/NF-κB pathway on integrin-associated protein (CD47) expression after myocardial infarction (MI) in rats. An MI Sprague Dawley rat model was established by ligating the left anterior descending coronary artery. The rats were divided into three groups: Sham, MI, and SB+MI (SB216763, a GSK-3β inhibitor) groups. Primary rat cardiomyocytes (RCMs) and the H9c2 cell line were used to establish in vitro hypoxia models. Immunohistochemistry was used to observe the changes in cardiac morphology. Quantitative real-time PCR and western blotting analyses were conducted to detect mRNA and protein expression levels of CD47 and NF-κB and apoptosis-related proteins, respectively. Apoptosis of hypoxic cells was assessed using flow cytometry. A significant reduction in the sizes of fibrotic scars was observed in the SB+MI group compared to that in the MI group. SB216763 decreased the mRNA and protein expression of CD47 and NF-κB during MI. Furthermore, SB216763 reduced the protein expression of CD47 and NF-κB in RCMs and H9c2 cells under hypoxic conditions for 12 h, and alleviated hypoxia-induced apoptosis. SN50 (an NF-κB inhibitor) also decreased CD47 protein expression in RCMs and H9c2 cells under hypoxic conditions for 12 h and protected cells from apoptosis. GSK-3β upregulates CD47 expression in cardiac tissues after MI by activating NF-κB, which in turn leads to myocardial cell damage and apoptosis.